SHARD: an improved method for staining and visualizing multiplex immunofluorescence in optically cleared postmortem human brain tissue - Rosen, Grace A.; Kirsch, Daniel; Nicks, Raymond; Kelley, Hunter; Mathias, Rebecca; Cormier, Kerry A.; Kubilus, Caroline A.; Dec, Bryan; Stein, Thor D.; Alvarez, Victor E.; Alosco, Michael L.; McKee, Ann C.; et al. (Frontiers in Neuroscience, 2024)
Postmortem human brain tissue is a critical resource for studying neurodegenerative disease, providing critical insights into cellular morphology, pathology, and network connectivity. To improve standard microscopy and enable high-resolution, three-dimensional (3D) images of tissues at the subcellular level, tissue-clearing methods have been developed. These 3D images allow for the analysis of large regions of interest and can be used to study structural and spatial changes that occur during neurodegeneration. Additionally, 3D imaging facilitates the visualization of whole-cell morphology, especially in cells with long processes that would otherwise be truncated in single-plane images. Human brain tissue is especially challenging for tissue clearing due to the abundance of lipids in myelin and the need for optimal fixation and low postmortem intervals. Formaldehyde-based fixatives, commonly used in preserving tissue, hinder antibody binding by crosslinking important antibody epitopes, and fluorescent microscopy requires the incorporation of fluorescent labels through passive diffusion or electrophoresis. Recent studies have focused on optimally fixed human brain tissue with short postmortem intervals, limiting the general applicability of these methods. To address these challenges, we developed SHARD (SHIELD, antigen retrieval, and delipidation), a simple and widely applicable method for clearing and labeling human brain tissue, which can be applied to long-term banked human brain tissue preserved in formaldehyde. SHARD is a novel addition to the SHIELD tissue clarification method, combining antigen retrieval, tissue clearing, and staining of 200-μm sections from long-term banked human brain tissue. The SHARD method is effective for postmortem intervals (PMIs) ranging from 10 to 72 h in multiple neurodegenerative diseases and control samples. In this study, we demonstrate that the SHARD method significantly enhances the immunostaining of glial fibrillary acidic protein (GFAP), an astrocytic cytoskeletal marker. Overall, the combination of antigen retrieval and tissue delipidation holds great potential for achieving detailed 3D immunostaining in long-term formaldehyde-fixed postmortem human brain tissue, opening new avenues for research and discovery.